KAJIAN BATU TERBANG UNTUK MENENTUKAN JARAK AMAN MINIMUM PELEDAKAN LAPISAN PENUTUP BATUBARA TERHADAP WILAYAH PERMUKIMAN - Handayana, Raden Haris; Shodik, Fajar; Salahudin, Sani (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2023)
Fly rock is a rock fragmentation that is thrown as a result of blasting. Such fragmentation that is thrown beyond the specified safe distance can cause a damage to the infrastructure, mechanical equipment and humans. This study aims to determine the safe radius of the fly rock that resulting from blasting residential area which that has a distance 200-300 m and has potentially distressing to cause damage. Calculating of the flying rock throwing distance is carried out theoretically and actually with orientation to the distance between spaces, the distance between burdens, minimum stemming height, minimum hole depth, powder factor, average charge blast hole and distance initial burdens. For theoretical calculations, the save distance is calculated by empirical methods and dimensional analysis. Results of the study shows that the maximum distance of the actual fly rock throw is 05.31 m and based on the predictions using the Cratering Method, the maximum distance of fly rocks is 172 m with a safety factor of 2 and the maximum distance of fly rocks is 199.04 m with a safety factor of 2. Based on the actual and predicted data above, it is not safe for blasting locations that is less than 200 m from residential areas, that refers to the safe radius threshold based on the regulation of the Minister of Energy and Mineral Resources No. 1827 K/30/MEM/2018.